(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this paper we analyze the social effects caused by the economic crisis in our country, mainly those associates with intense and terrible increase in unemploymentand the various responses and social policy commitments in a context of clear deterioration in public finances. For the future, it would be necessary austerity andgreater levels of efficiency and effectiveness in public action to reduce macroeconomicimbalances in our economy.